A development of online system for policy and procedure using open Architecture Community System (OpenACS) / Mohd Khaizul Azhar Mohd Yusof - Mohd Yusof, Mohd Khaizul Azhar (2006)
The usage of policy and procedure management system becomes more important in organization. People are realizing that policy can help their organization move on forward better. But unfortunately the way they manage the policy is not suitable. At the current status, office management especially for handling policy and procedure is using manual system. They are not using proper method and thus a lot of problems arise. Namely Online System for Policy and Procedure (OSPP), this system was developed to overcome the problems and fulfill the requirement for handling policy in organization. The project was started by considering the problem faced by staff from FTMSK, UiTM and other factor that effecting the environment of system development. By using Open Architecture Community System (OpenACS) as the development platform, OSPP will provide better and comprehensive approach in managing policy and procedure. From the comparison between OpenACS and other framework, it does give a more advantage and suitable as a system platform based on its useful criteria. OSPP has a lot of features that can help person who are in charge of the policy management.